Continuance Intention of Augmented Reality Textbooks in Basic Design Course - Jiang-Jie Chen; Yen Hsu; Wei Wei; Chun Yang (MDPI AG, 2021)
The Basic Design course can help students understand design principles and visual art elements It is a compulsory basic course for the department of art and design in many universities. In recent years, Augmented Reality (AR) technology has found its way into the field of design education and has become a popular textbook tool in teaching courses. There are not many pieces of research on the application of AR in design courses. Therefore, this study attempts to explore the factors that affect students' acceptance of AR textbooks in Basic Design course and their continuance intention for AR textbooks. This study first focused on students with experience in using AR textbooks. Open-ended questions were used to collect factors that allow AR textbooks to be used in the design curriculum; then questionnaire surveys and factor analysis were conducted and the research hypotheses are presented. Then, the research hypotheses were verified through reliability and validity as well as structural equation modeling. Three factors and 15 items for students to accept AR textbooks in the Basic Design course were summarized in the research results, including the three factors named "Visual Attraction", "Knowledge-ability", and "Situational Experience". The analysis of differences showed significant differences in gender among these three factors and no significant differences between grades and departments. Also, it was found from the analysis results of the structural equation model that the factors of "Visual Attraction" and "Knowledge-ability" both had a positive effect on the continuance intention, of which "Knowledge-ability" was the most important influencing factor. The results of this study can help the application and development of AR textbooks in the Basic Design course.